Saltwater intrusion ecophysiological effects on Pseudophoenix sargentii, Roystonea regia, Sabal palmetto “Lisa,” and Thrinax radiata in South Florida - Khoddamzadeh, Amir Ali; Flores, Jason; Griffith, M. Patrick; Souza Costa, Bárbara Nogueira (Frontiers in Ecology and Evolution, 2023)
Climate change will alter natural areas on a global scale within the next century, especially in low-lying coastal areas where sea-level rise is predicted to severely degrade or destroy many ecosystems. As sea-level rise continues, it is expected that salinity due to saltwater intrusion will impact soil health and agricultural production, this is of even greater importance in areas such as South Florida where the surface and groundwater resources are hydrologically connected due to the shallow and highly permeable limestone soils. The chlorophyll concentrations in leaf tissue were chosen as the primary health indicator to assess whether this is a valuable factor to consider for plant health risk assessment and whether optical sensor technology such as the SPAD and NDVI, are valuable tools when understanding the impact seawater encroachment has on plant nitrogen uptake. Therefore, the aim of this study was to evaluate the effects of salt concentrations on plant growth and health of four palm species. The treatments were fresh water represented by the concentrations 0 ppt served as the control, and 0.5 ppt. Brackish water was represented by concentrations 5, 10, and 15 ppt. Oceanwater was represented by the concentration 25 ppt. Hypersaline water was represented by 50 ppt. The experiment was established in a completely randomized design with seven treatments was replicated 5 times with single pot replications (one plant in each pot), totaling 35 plants per species. Data were subjected to analysis of variance (ANOVA)and the means compared by Tukey’s test (p≤0.05) using the SISVAR statistical program. The growth parameters and chlorophyll content were reduced over time, particularly at higher salt concentrations for all palm species studied. The species R. regia was very susceptible to salinity, and the palm S. palmetto is more susceptible to salinity than the T. radiata and P. sargentii palms.